Inovasi Pelayanan Publik Diskominfo Kota Samarinda di Era Disrupsi: Studi Implementasi Layanan Samarinda Siaga 112 dan Panic Button - Apriani, Fajar; Rahma, Ukik Aisya; Yusuf, Muhammad; Hayati, Sri; Jubaidah, Jubaidah; Suraya, Rizky (Universitas Batanghari Jambi, 2024)
In the current era of disruption, the implementation of the Samarinda Siaga 112 Service and the panic button developed by the Samarinda City Communication and Information Service are available as a forum for optimizing public services in terms of handling electronic-based emergencies. Through a qualitative descriptive approach, this research examines the implementation of the Samarinda Siaga 112 and panic button services which refer to Samarinda Mayor Regulation Number 52 of 2019 concerning the Implementation of a Single Emergency Call Number 112 and Panic Button, by focusing on aspects of communication, resources, disposition, bureaucratic structure and the obstacles. This research found that the Samarinda Siaga 112 and panic button services have been implemented well even though there was a decrease in the number of complaint channels after Covid-19 ended because the Samarinda Siaga 112 and panic button services were much more needed during the past Covid-19 pandemic. The operational functioning of this service is reduced andi s still hampered by other obstacles related to technical matters and the characterictics of the population of Samarinda City with the finding that 75,54 percent of incoming callas to Emergency Call 112 are fake calls. However, this service can still be implemented effectively by optimizing existing resources, and contuining to be committed to improving information technology-based public services for the communication in handling various emergency incidents. The role of emergency volunteers is also very significant in implementing this service and better empowerment efforts need to be carried out by the Samarinda City Government. More massive educational efforts are also needed for the people of Samarinda City regarding the urgency of caring and being alert to emergency condotions as well as using media in public service communication wisely and beneficially for others.